Response of Plant Immunity Markers to Early and Late Application of Extracellular DNA from Different Sources in Tomato (Solanum lycopersicum) - Ireri Alejandra Carbajal-Valenzuela; Rosario Guzmán-Cruz; Mario M. González-Chavira; Gabriela Medina-Ramos; Luz María Serrano-Jamaica; Irineo Torres-Pacheco; Lucía Vázquez; Ana Angelica Feregrino-Pérez; Enrique Rico-García; Ramón Gerardo Guevara-González (Agriculture, 2022)
As a recently explored agricultural practice, the controlled elicitation of plants offers high potential in multiple crop needs as growth promotion, activation of defenses and the production of specific metabolites. Extracellular DNA has been identified as a plant immune system elicitor but some aspects of the plant response have not been explored. In the present work, five DNA treatments were applied in tomato plants and the response of catalase, superoxide dismutase, phenylalanine ammonia lyase activities, hydrogen peroxide, total phenolics and flavonoid contents in leaves were spectrophotometrically measured. Treatments differed by the source and concentration of DNA and plant phenological stage of application. Furthermore, mathematical modeling and principal component analysis were performed to explore the behavior of each variable and their interaction. The most effective treatment was the self-DNA application in young plants based on the intensity and duration of immune system activation. The information given by the measured variables correlated positively with the phenylpropanoid pathway markers and negatively with catalase and superoxide dismutase activities. Results reported here propose an easy way to evaluate plant immune response activation by DNA and any other elicitor and provide useful information for future development of controlled elicitation strategies in crop production.